Diagnostic radiology methods for assessing coronary artery bypass graft viability - Zh. V. Vesnina; E. V. Grakova (Бюллетень сибирской медицины)
The review describes available modern radiological methods which are currently applied for a detailed and comprehensive anatomical and functional assessment of the viability of various coronary artery bypass grafts. In addition, it presents some aspects of the implementation of these methods and clinical interpretation of the results.